PRODUKSI BERITA TEMPO: TELAAH ANTROPOLOGI MEDIA - , RINA WIDIASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is motivated by the emergence of the issue about mediaâs independence value. This value became dominant among Indonesian journalists at the beginning of the New Order. The value emerged as a dialectical response towards the subordination of the media by the government and political parties in the reign of the guided democracy system. Since the Tempo is a weekly news magazine that was born in that particular era and becomes one of the most powerful media in maintaining its independence, this study aims to understand how the Tempo internalizes and disseminates the value of independence itself. To have a good grip on the issue, this study uses anthropological approach to media. The approach assumes that the process of news production is equal to a process of meaning production. Therefore, the context of media production activities that takes place daily in the Tempo becomes the material object in this research. The choice of this approach requires the use of ethnographic methods relying substantially to participant observation, in-depth interviews, and literature as data collection technique. Data analysis was performed with the assistance of theoretical concepts in data classification and interpretation in relationships between groups of data. The result of this study indicates that the value of independence in the Tempo is built by its journalists. The forming of independent journalist in Tempo happens in the liminal situation, anti-structural, and communal social bonds. However, the Tempo as a modern organization also establishes a structural and hierarchical system of social relations that generates subordination and dependency to appear. The structural demands become greater along with the expansion of the Tempo media itself. Throughout its history, the Tempo is constantly engaged in the tensions and negotiations between the two tendencies of social relations and values i.e. communal and structural social relations, and the value of independence and dependency. Business expansion is interpreted as a way to gain economic independence as a prerequisite to be able to defend the independence of the media. Keywords: Values, News Production Process, Liminal, Community, and Social Structure